2015
DOI: 10.1002/ppul.23229
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of invasive and noninvasive ventilation in children less than 1 year of age: A long‐term follow‐up study

Abstract: Based on this long-term follow-up study, NiPPV use in infants appears to be a viable long-term ventilation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…Their main reasons for initiating LTV were lower respiratory airways diseases (55% on NIV; 10% on IMV), and spinal cord injury (50% on IMV). Our results are similar to those of many studies performed especially in western, more developed and with high-income countries [8][9][10][11][12][13][14][16][17][18][19][20]. Differences between studies may vary depending on several factors such as the availability of local facilities and skills; differences of inclusion criteria in the main diagnostic categories considered, and collaborations with referral.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Their main reasons for initiating LTV were lower respiratory airways diseases (55% on NIV; 10% on IMV), and spinal cord injury (50% on IMV). Our results are similar to those of many studies performed especially in western, more developed and with high-income countries [8][9][10][11][12][13][14][16][17][18][19][20]. Differences between studies may vary depending on several factors such as the availability of local facilities and skills; differences of inclusion criteria in the main diagnostic categories considered, and collaborations with referral.…”
Section: Discussionsupporting
confidence: 88%
“…In our logistic regression, IMV was likely associated with younger age at starting ventilatory support (p = 0.0220) and receiving [12,14,17]. Only Kherani et al [13], reported no differences comparing the age of initiation of ventilation in the NIV and IMV groups in children less than 1 year. Racca et al [17], reported that IMV was significantly related to younger age, longer time spent under mechanical ventilation, and neuromuscular disorders or hypoxic (ischemic) encephalopathy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Over the last decade, the use of long‐term, non‐invasive respiratory support has increased in children with chronic respiratory failure, likely due to its increased acceptance for certain populations, such as those with neurologic and neuromuscular conditions, as well as the increased availability of portable, high‐efficiency positive pressure devices and non‐invasive interfaces. Single‐site studies suggest that over 75% of children are initiated on non‐invasive respiratory support in the inpatient setting, often non‐electively . Despite the increased use of non‐invasive respiratory support, some patients with severe or progressive conditions ultimately cannot be supported without transtracheal ventilation.…”
Section: Discussionmentioning
confidence: 99%